Combustion Characteristics of Premixed Hydrogen/Air in an Undulate Microchannel - Pedro R. Resende; Leandro C. Morais; Carlos Pinho; Alexandre M. Afonso (Energies, 2022)
This work reports a numerical investigation of microcombustion in an undulate microchannel, using premixed hydrogen and air to understand the effect of the burner design on the flame in order to obtain stability of the flame. The simulations were performed for a fixed equivalence ratio and a hyperbolic temperature profile imposed at the microchannel walls in order to mimic the heat external losses occurred in experimental setups. Due to the complexity of the flow dynamics combined with the combustion behavior, the present study focuses on understanding the effect of the fuel inlet rate on the flame characteristics, keeping other parameters constant. The results presented stable flame structure regardless of the inlet velocity for this type of design, meaning that a significant reduction in the heat flux losses through the walls occurred, allowing the design of new simpler systems. The increase in inlet velocity increased the flame extension, with the flame being stretched along the microchannel. For higher velocities, flame separation was observed, with two detected different combustion zones, and the temperature profiles along the burner centerline presented a non-monotonic decrease due to the dynamics of the vortices observed in the convex regions of the undulated geometry walls. The geometry effects on the flame structure, flow field, thermal evolution and species distribution for different inlet velocities are reported and discussed.